KENDALA IMPLEMENTASI KURIKULUM MERDEKA YANG DIHADAPI GURU PENDIDIKAN ANAK USIA DINI DI JEMBER - Andini, Yuli Tri; Syarifatul Umami, Yuniarta; Afandi, Ahmad; Ratna Pratiwi, Elok (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to examine the obstacles to implementing the independent curriculum faced by early childhood education teachers. This research uses a descriptive qualitative method with a case study type. This research uses the Miles & Huberman analysis technique. The sample in this research was 10 early childhood teachers in 4 early childhood institutions using purposive sampling techniques. Data collection techniques are interviews and questionnaires. Indicators for questions and questionnaires are participation in independent curriculum seminars/counseling, understanding new terms in the independent curriculum, implementation of the independent curriculum in school institutions. The results obtained are that there are still few teachers who take part in seminars on the independent curriculum, so that teachers' understanding of mastering new terms in the independent curriculum is still unfamiliar, the implementation of the independent curriculum still uses the term transition curriculum so that the implementation carried out in institutions is still in the term transition curriculum 2013 curriculum towards an independent curriculum. Keywords: Independent curriculum, Early Childhood teacher.